an-Naqd ‘ala Tarjamati Kitab ‘Izah an-Nasyiin li Mustafa al-Ghulayaini - Hanun Khiyarotun Nisa’ (Postgraduate of IAIN Metro Lampung Indonesia, 2019)
The Book of ‘Izah an-Nasyiin is a collection of writings written by one of the great Egyptian scholars, Mustafa al Ghulayaini, in the newspaper